2017
DOI: 10.1016/j.redox.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel redox regulator, MnTnBuOE-2-PyP5+, enhances normal hematopoietic stem/progenitor cell function

Abstract: The signaling of reactive oxygen species (ROS) is essential for the maintenance of normal cellular function. However, whether and how ROS regulate stem cells are unclear. Here, we demonstrate that, in transgenic mice expressing the human manganese superoxide dismutase (MnSOD) gene, a scavenger of ROS in mitochondria, the number and function of mouse hematopoietic stem/progenitor cells (HSPC) under physiological conditions are enhanced. Importantly, giving MnTnBuOE-2-PyP5+(MnP), a redox- active MnSOD mimetic, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 44 publications
2
56
0
Order By: Relevance
“…The activity of Keap1/Nrf2 pathway increases in response to oxidative stress and leads to upregulation of antioxidant genes to combat oxidative stress in several fibrosis models [ 55 , 56 , 57 , 58 , 59 ]. Others have also reported that the Nrf2 pathway is enhanced with manganese porphyrin treatment [ 30 , 60 , 61 ]. We speculate that this increase in NQO1 levels by MnTE-2-PyP primes the cells for a cytotoxic event such as radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of Keap1/Nrf2 pathway increases in response to oxidative stress and leads to upregulation of antioxidant genes to combat oxidative stress in several fibrosis models [ 55 , 56 , 57 , 58 , 59 ]. Others have also reported that the Nrf2 pathway is enhanced with manganese porphyrin treatment [ 30 , 60 , 61 ]. We speculate that this increase in NQO1 levels by MnTE-2-PyP primes the cells for a cytotoxic event such as radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be hypothesised that pharmacological mitigation of the accumulation of ROS could be also an interesting strategy to improve BM transplantation. In fact, a recent report shows that limiting mitochondrial oxidative stress with a MnSOD mimetic improves the function of HSCs in animal models of haematopoietic transplantation [ 212 ]. These findings encourage further studies for improving transplantation through modulation of ROS levels.…”
Section: The Use Of Ros As a Therapeutic Target In Haematological Malmentioning
confidence: 99%
“…While MnTnHex-2-PyP 5+ is a potent SOD mimetic, most recent studies point to its role and role of its porphyrin analogs (MnTE-2-PyP 5+ and MnTnBuOE-2-PyP 5+ ) in the modification of the activity of transcription factors including nuclear factor kappa B (NF-κB) and nuclear factor E2-related factor 2 (Nrf2) [ 22 , 43 , 44 , 45 , 46 ] and different mitogen-activated protein kinases, such as extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK), protein kinase B (AKT) and p38 mitogen-activated protein kinase (p38-MAPK) [ 8 , 45 , 47 ]. Several studies provided evidence that this and other potent cationic porphyrin-based SOD mimics (such as MnTE-2-PyP 5+ and MnTnBuOE-2-PyP 5+ ) modify protein cysteines of transcription factors [ 44 , 45 , 46 ], MAPK, and protein phosphatase 2A through their S-glutathionylation, thereby modifying their activities [ 45 , 47 ]. We have provided the evidence and the mechanistic basis that the SOD-like potency of Mn porphyrins is proportional to their ability to S -glutathionylate cysteines of proteins [ 6 , 29 , 47 ].…”
Section: Introductionmentioning
confidence: 99%